PERILAKU CREEP PADA KOMPOSIT POLYESTER DENGAN SERAT KULIT BAMBU APUS (GIGANTOCHLOA APUS (J.A & J. H. SCHULTES) KURZ) - Taufik, M.Ikhsan; Sugiyanto, .; Zulhanif, . (FT UNILA, 2013)
Bamboo is used as raw material wicker and crafts are emerging as a new solution for use as new materials that are more environmentally friendly and have better mechanical strength. Research by utilizing bamboo as reinforcement fibers and polyester resin matrix aims to determine the mechanical strength of the resulting composite merging the two. Bamboo fiber composites made with various volume fractions of 10%, 15% and 20% using polyester resin and catalyst MEKPO ratio 100:1. The composite is prepared by hand lay-up by using a glass as a mold. Bamboo fibers used as reinforcement composites, is expected to increase the tensile strength and creep strength of each variation. In addition to observing the microstructure using SEM (Scanning Electron Microscope) to determine the failure mechanisms that occur on the fracture surface.From this study the authors concluded that bamboo fiber composites have the potential for further development because the tensile test results are directly proportional to the addition of fiber to the highest tensile strength was 86.01 MPa at 20% volume fraction, whereas the average creep testing best time of 529.63 seconds on 10% volume fraction, the failure mechanism of the plates shown in SEM is a form of fiber breaking, pull out and de bonding.Keywords: Bamboo, composite, creep.